Effect of abusive supervision on pro-social citizenship behaviors: The mediating role of interactional justice, organization-based self esteem and meaning of work - Farah Samreen; Amir Rashid; Mahmood Bodla (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The aim of the present study is to check the effect of abusive supervision on pro-social silence and pro-social voice through three mediating variables¯interactional justice, meaning of work and organization based self-esteem in the context of Pakistan. Data were collected from 917 subordinate-supervisor dyads from Pakistan. Results from structural equation modeling revealed that only interactional justice partially mediates the negative relation of abusive supervision with pro-social voice pro-social silence, whereas meaning of work and organization-based self-esteem did not show significant mediating effects. The present study will broaden the existing literature regarding the effect of abusive supervision on pro-social voice and pro-social silence¯ the two very distinct and essential forms of OCB considering the boundary conditions of a developing Asian country such as Pakistan. Conducting such study in Pakistan clarifies the difference in the attitude and the reaction of employees against abusive supervision in a developing Asian country, as these cultures are featured by high power distance and unemployment that affect these behaviors differently effect of abusive supervision on pro-social citizenship behaviors: the mediating role of interactional justice, organization based self-esteem and meaning of work.
Keywords: 330; abusive supervision; interactional justice; organization based self-esteem; meaning of work; subordinate rated pro-social silence; supervisor rated pro-social voice